An investigation of the mechanism of ZiyinDianji decoction in treating follicular dysplasia based on network pharmacology and molecular docking: ZYDJD in treating follicular dysplasia - Feng, Xue; Zhou, Huifang; Lu, Wentian; Liu, Xinyuan; Wu, Yue; Dai, Yaxin (Cellular and Molecular Biology, 2023)
Follicular development disorder is a common gynaecological endocrine disease that can cause infertility, menstrual disorders, abortion, and other complications. ZiyinDianji decoction (ZYDJD) is a commonly used traditional Chinese medicine in clinical practice to promote follicular growth and development, but its pharmacological activity and mechanism of action are not clear. We combined network pharmacology with molecular docking and in vivo animal experiments to investigate the mechanism of ZYDJD in follicular development disorder. Cytoscape software was used for constructing ZYDJD-active component-target and PPI networks. GO biological process and KEGG pathway enrichment analyses were performed. The main components and key targets were selected for molecular docking. Finally, animal experiments were conducted for validation. The network pharmacology results showed that ZYDJD contained 83 active components and 159 core targets. The six most important active components were quercetin, luteolin, kaempferol, baicalein, isorhamnetin, and β-sitosterol, and the most important disease targets were AKT1, TNF, IL-6, and P53. GO analysis mainly involved 470 cell biological processes, including effect on hormones, vascular morphogenesis, development, and cell proliferation. KEGG analysis involved cancer pathways, lipid metabolism pathways, and PI3K/AKT signalling pathways. Molecular docking showed good results, and animal experiments further verified that ZYDJD prevented cyclophosphamide from causing excessive activation of primordial follicles. ZYDJD maintained ovarian reserve and reproductive function by inhibiting the hyperphosphorylation of key molecules of the PI3K/Akt pathway, reducing FOXO3a, thereby ensuring the development of normal follicles. In conclusion, based on network pharmacology, molecular docking, and animal experiments, ZYDJD may act through the PI3K/Akt/FOXO3a pathway.